Elevated concentrations of perfluorohexanesulfonate and other per- and polyfluoroalkyl substances in Baiyangdian Lake (China): Source characterization and exposure assessment. (October 2018) - Cui, Qianqian; Pan, Yitao; Zhang, Hongxia; Sheng, Nan; Dai, Jiayin
Abstract: Novel 6:2 chlorinated polyfluorinated ether sulfonate (6:2 Cl-PFESA) and legacy PFASs, such as perfluorohexane sulfonate (PFHxS), have been used to replace perfluorooctane sulfonate (PFOS), a known persistent organic pollutant. Thus, it is critical to understand these PFOS alternatives regarding their sources and concentrations in the natural environment. In this study, 41 surface water samples as well as edible aquatic organisms were collected from Baiyangdian Lake, the largest freshwater lake in Hebei Province, China. Perfluorooctanoate acid (PFOA) and PFHxS were the predominant PFASs detected in the surface water, reaching concentrations of 8 397.23 ng/L and 1 478.03 ng/L, respectively, with PFHxS accounting for the greatest proportion (∼80.00%) in most water samples. PFHxS (mean: 87.53 ng/g) and PFOS (mean: 35.94 ng/g) were also the most prevalent compounds detected in aquatic organisms. Estimated daily intake (EDI) values of PFOS (16.56 ng/kg bw/d) and PFHxS (16.11 ng/kg bw/d) via aquatic food and drinking water were the highest among PFASs, indicating potential exposure risks to residents. In addition, fish product consumption was the important exposure pathway for residents to PFOA, PFHxS, PFOS, and 6:2 chlorinated polyfluorinated ether sulfonate (6:2 Cl-PFESA). This study reports on the highest PFHxS levels ever recorded in surface water, suggesting that further quantification of PFHxS in human serum and assessment of its health risks to local residents are warranted and critical. Graphical abstract: Highlights: High levels of PFOA and PFHxS were detected in Baiyangdian Lake surface water. High-level PFASs were found in duck blood and liver. Fish consumption is an important source of exposure to PFOA/S, PFHxS and 6:2 Cl-PFESA. The estimated daily intakes of PFOS and PFHxS are both near 16 ng/kg bw/d. Abstract : PFHxS was the predominant PFAS detected in surface water and aquatic organisms, with its estimated daily intake (EDI) suggesting potential exposure risks to residents.